SPATIAL ANALYSIS OF PHYSICO-CHEMICAL PARAMETERS OF WATER AND SOIL IN THE KUALA LANGSA MANGROVE ECOSYSTEM, ACEH - Muhammad Fauzan Isma (Geographica: Science and Education Journal, 2025)
Mangrove ecosystems play a vital role in maintaining coastal ecological balance through their biological, hydrological, and economic functions. However, increasing anthropogenic activities such as aquaculture, settlement expansion, and infrastructure development have led to environmental degradation in the mangrove areas of Kuala Langsa, Aceh. This study aims to analyze the physicochemical characteristics of water and soil in three mangrove zones—ecotourism, residential, and airport areas—by measuring parameters such as temperature, oxidation-reduction potential (Eh), water and soil pH, salinity, and moisture content. Field sampling was conducted in situ in February 2024 using a purposive sampling method, while data analysis was performed descriptively and quantitatively. The results show that Station 1 (Mangrove Ecotourism Area) exhibited the best environmental conditions, with an average temperature of 30 °C, Eh of 141.67 mV, water pH of 7.14, soil pH of 6.34, salinity of 33‰, and soil moisture of 67.6%. Station 2 (Residential Area) experienced higher anthropogenic pressure, indicated by higher temperature (33.33 °C), negative Eh (-159.33 mV), and lower salinity (2‰). Meanwhile, Station 3 (Airport Area) showed stable environmental conditions with a positive Eh (115.33 mV), neutral pH, salinity of 2.5‰, and moisture of 32.33%. Overall, the Kuala Langsa mangrove ecosystem still demonstrates a good degree of ecological resilience, although some areas have experienced degradation due to human activities. This study highlights the importance of ecosystem-based adaptive management through domestic waste control, tourism activity regulation, and mangrove vegetation conservation as ecological buffer zones to sustain the environmental functions of coastal ecosystems.